Directions for effective use of forest resources in Ukraine - Свинтух, Мар'яна Богданівна (Baltic Journal of Economic Studies, 2016)
Purpose. The aim of the article is determination and substantiation of directions of rational use of forest resources in Ukraine. Methodology of research. The theoretical and methodological basis of conducted research is the provision of economic theory, sustainable development, environmental economics and economics forest exploitation. The following methodological tools and techniques were used to achieve this goal: methods of analysis and synthesis (to identify problems of the relationship for using potential of forest resources with factors of influence on their reproduction, the studying essence of the term “forest resources”); monographic – to study the experience of forming rational use of forest resources and wood waste; systematic approach (in substantiating the use of instruments for regulation forest exploitation); scientific abstraction (in the study of capabilities to ensure the process of rational reproduction of forest resources); graphic (for visual images of some analytical observations). Results. Theoretical approach to forest regeneration as a major task in forest anagement, which includes the integrated use of all available organizational and technological measures to facilitate its natural regeneration has been formulated. It has been established the regularity of ensuring the efficient use of waste wood in places of billets, identified and systematized its forms for future use. The methodical approach to assess the effect of using wood waste for fuel production and related products during processing on the harmonization of economic and environmental interests in the area of forest exploitation has been formulated. Practical implications. The obtained results are the basis for solving practical problems of integrated management of forest resources in Ukraine, waste of forest felling in the places of timber harvesting and also for development of the system of measures to improve the ecological and economic mechanism of development of nature protection territories and formation on this basis effective policy of nature use according to the national interests of Ukraine. It will promote increasing the economic efficiency and the reasonableness of decisions related with priority directions of natural resource policy in terms of transformation of the national economy. Value/originality. It has been established the application of fuel wood in the production of bio-fuels through the establishment of plantations of fast-growing woody species for industrial forest growing for energy purposes.
Keywords: forest complex; forest resources; forest exploitation; forestry; wood waste; forest billet; plantations of fast-growing woody species